Peran Tenaga Kesehatan dalam Melaksanakan Pelayanan Kesehatan WBP Rutan - Ruth Faeriani Telaumbanua (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
This research focuses on the role of health workers in carrying out health services for WBP in Detention Centers. The research method used is a qualitative approach. Data collection techniques used are field research by conducting interviews and observations as well as literature studies. Based on the results of research conducted it is known that the role of health workers in detention centers is in accordance with their main duties and functions. Detention centers have a Polyclinic as a place for the implementation of health services in detention centers. In addition in the implementation of health services, there is an MoU between the detention center and the Government. In this case the provision of free health services with a National Identity Card (KTP) at a government-owned health agency. In addition, the detention center supports the implementation of the National Health Insurance for Penitentiary Guides in the Detention Center. But in the implementation of health services, the role of health workers does not run optimally because health workers in detention centers are only nurses' medical backgrounds, besides the lack of supporting infrastructure. After analyzing various facts, several alternative solutions were found to be done by: increasing the number of human resources for medical doctors in detention centers. Each disease experienced by WBP can be directly dealt with in detention centers and the addition of infrastructure facilities so that the role of health workers in the implementation of health services in Detention center can run optimally.